2022
DOI: 10.1002/ghg.2164
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the interaction between typical amines and alkaline minerals for improved CO2 absorption and mineralization

Abstract: Amine scrubbing is a mature technology to cut down CO2 emissions from human activities but suffers from a high energy consumption of solvent regeneration. The integrated CO2 absorption and mineralization (IAM) process can effectively reduce the energy consumption of amine regeneration by replacing traditional thermal regeneration with chemical regeneration via CO2 mineralization. However, a fundamental understanding of the interaction between typical amines and alkaline minerals was still lacking. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that using Ca(OH)2 as an auxiliary agent in the absorption of CO2 by amines can convert CO2 into the mineral product carbonate, thus effectively reducing and reusing the emitted CO2 (Zhang et al 2020). Another study (Ji et al 2022) aimed to gain insight into the interaction between typical amines and alkaline minerals, particularly the effect of amine type on amine regeneration, alkaline metal leaching, and CaCO3 precipitation. The results of a series of studies have shown that the structural properties of amines influence the formation of CaCO3 crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that using Ca(OH)2 as an auxiliary agent in the absorption of CO2 by amines can convert CO2 into the mineral product carbonate, thus effectively reducing and reusing the emitted CO2 (Zhang et al 2020). Another study (Ji et al 2022) aimed to gain insight into the interaction between typical amines and alkaline minerals, particularly the effect of amine type on amine regeneration, alkaline metal leaching, and CaCO3 precipitation. The results of a series of studies have shown that the structural properties of amines influence the formation of CaCO3 crystals.…”
Section: Introductionmentioning
confidence: 99%